UPAYA PENINGKATAN MUTU PENDIDIKAN: MANAJEMEN PESERTA DIDIK DI MADRASAH TSANAWIYAH (MTs) AN-NIZHAM KOTA JAMBI - Summiyani; Hilmi; Yuliana Afifah; Fransisko Chaniago (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
Student management is a crucial aspect in improving the quality of education. It involves the efficient and effective management of all activities related to students and other resources to achieve educational goals. The main objective of this research is to analyze the planning, development, and evaluation of students at Madrasah Tsanawiyah An- Nizham in Jambi City. This study uses a qualitative research approach. Data collection was carried out through observation, interviews, and documentation methods, involving the head of the madrasah, teachers, and the committee. The results of this research reveal that, first, the planning analysis at Madrasah Tsanawiyah An-Nizham in Jambi City includes ari analysis of prospective students' needs, the admission process, student selection, orientation, placement, grouping, and student reporting. Second, the development efforts include instilling discipline through dhuha prayer every morning, leadership training in organizational activities, and counseling provided by guidance counselors. Third, student evaluation uses benchmarks to calculate students' achievement scores and evaluates curricular and extracurricular outcomes as measures to assess students' development according to their talents and interests.